Performance comparison of thermoelectric generators with Extremum seeking control and incremental conductance MPPT methods - Twaha, Ssennoga; Zhu, Jie; Yan, Yuying (2017)
Thermoelectric generators (TEGs) are used for converting heat into electricity, environmentally friendly, without moving parts and with less complexity. One of the problems with TEG is that it has low efficiency and therefore it is necessary to harvest maximum power from them to ensure their optimum utilization. Therefore, it is required to use the maximum power trackers (MPPTs) which for long time have demonstrated good performance in photovoltaic systems. The purpose of this work is to compare the performance of Extremum seeking control (ESC) algorithm with a classical incremental conductance (IC) method. Results indicate that ESC outperforms the IC technique in terms of extracting maximum power and the speed of computation. ESC method is faster than the IC method with simulation time of 152.1s and 781.8 s respectively. Moreover ESC is less complex in terms of model implementation than the IC method.